Ceramic diaphragm as well as preparation method and application thereof

By using modified ceramic particles to form a polymer cladding layer and adding porous nanoceramics of different particle sizes in the ceramic separator, the ionic conductivity and thermal stability of the ceramic separator are solved, and the safety and performance stability of the battery are achieved at high temperatures.

CN120389204APending Publication Date: 2025-07-29SHANXI HOUSHENG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202510338083.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

The existing ceramic diaphragms have poor ionic conductivity and thermal stability, resulting in the risk of short circuits or explosions at high temperatures.

Method used

Modified ceramic particles are used to form the first coating of the polymer clad layer, and porous nanoceramics of different particle sizes are added to the second coating to form a ceramic separator with excellent electrical conductivity and high thermal stability.

Benefits of technology

The puncture resistance and heat resistance of the ceramic diaphragm are improved, ensuring the stability of the battery and the sustainability of the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120389204A_ABST
    Figure CN120389204A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic diaphragm as well as a preparation method and application thereof. The ceramic diaphragm comprises a base membrane, a first coating arranged on the surface of at least one side of the base membrane, and a second coating arranged on the surface of the first coating, the first coating comprises modified ceramic, a dispersing agent, a thickening agent, a binding agent and a wetting agent; the second coating comprises porous nano ceramic, a dispersing agent, a thickening agent, a binding agent and a wetting agent. The ceramic diaphragm disclosed by the invention has good high temperature resistance, and the puncture resistance of the ceramic diaphragm is improved due to the addition of the modified ceramic containing the polymer coating layer; meanwhile, by adding the porous nano ceramics with different particle sizes, the heat resistance of the diaphragm is improved under the condition that the air permeability of the diaphragm is not influenced, and the stability of the battery performance is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new materials, and particularly relates to a ceramic separator and a preparation method and application thereof. Background Art

[0002] In the battery industry, lithium-ion batteries have always occupied a crucial position due to their high efficiency and wide applications. As one of the four key materials of lithium batteries, the separator not only plays a role in separating the positive and negative electrodes structurally to prevent battery short circuits, but also allows lithium ions to freely transfer in the electrolyte. At the same time, it can regulate the flow of the electrolyte and the ion transport rate inside the battery, thereby controlling the charge and discharge rate and cycle life of the battery. Currently, polyolefin separators are generally used in lithium-ion batteries because of their strong chemical stability and high mechanical strength, etc. However, due to their poor heat resistance, they may melt under overcharge, over-discharge, rapid charge and discharge, or high temperature, causing short circuits, fires, or even explosions. In order to improve the thermal stability of polyolefin separators, a ceramic coating with strong thermal stability is generally coated on the surface of polyolefins to make a ceramic separator, which can significantly increase the thermal stability of the separator at high temperatures. The ceramic coating is generally prepared by mixing ceramic particles (such as alumina, silica, magnesia, etc.), binders (such as PVA, PVDF, etc.), solvents, and surfactants according to a certain formula.

[0003] For example, CN104485438A discloses a ceramic separator with a high inorganic solid content. The ceramic separator is a non-porous membrane composed of a composite material, including inorganic nanofibers and a binder. The mass of the inorganic nanofibers accounts for 45%-80% of the total mass of the separator. The average length of the inorganic nanofibers is 0.5-2 microns, and the average diameter is 50nm-300nm. The pores of the ceramic separator are formed by the random stacking of inorganic nanofibers, with an average pore diameter between 0.05μm and 1μm and an average porosity between 40% and 60%. The ceramic separator made by this method is difficult to have both good bonding strength and air permeability.

[0004] For example, CN108649168A discloses a preparation method of a hollow microsphere ceramic-coated separator. Using hollow microspheres with a diameter of 0.5μm-10μm as the main material to coat the battery separator can reduce the air permeability of the coating. However, due to the large gaps between the particles in the low-thickness coating, the thermal shrinkage performance of the coated separator is poor. Summary of the Invention

[0005] In view of this, the purpose of the present invention is to provide a ceramic separator and a preparation method and application thereof, so as to solve the problems such as poor ionic conductivity and thermal stability of ceramic separators in the prior art.

[0006] To achieve the above purpose, the technical solution of the present invention is realized as follows:

[0007] A ceramic separator, comprising:

[0008] A base film,

[0009] A first coating disposed on at least one surface of the base film,

[0010] And a second coating disposed on the surface of the first coating;

[0011] The first coating includes a modified ceramic; the second coating includes a porous nano-ceramic.

[0012] The first coating and the second coating further include a dispersant, a thickener, a binder, and a wetting agent.

[0013] The base film is a porous thin film, preferably one of a PE film, a PP film, and a PP / PE composite film.

[0014] The thickness of the porous base film is 1 μm - 20 μm, preferably 5 μm - 16 μm; the single-sided thickness of the first ceramic coating is 0.2 μm - 3 μm, preferably 0.5 μm - 2 μm; the single-sided thickness of the second ceramic coating is 0.2 μm - 3 μm, preferably 0.5 μm - 2 μm.

[0015] The modified ceramic is obtained by in-situ polymerization of a polymer coating layer on the surface of ceramic particles by a modifying solution; the material of the ceramic particles is selected from one or more of alumina, boehmite, zirconia, silica, magnesia, titania, zinc oxide, and calcium oxide.

[0016] The modifying solution includes a modifier pyrrole, an oxidant ammonium persulfate, and a solvent water or ethanol.

[0017] The porous nano-ceramic includes small-particle-size porous nano-ceramics and large-particle-size nano-ceramics; the small-particle-size porous nano-ceramics are one or more of porous nano-alumina, porous nano-boehmite, porous nano-zirconia, porous nano-silica, porous nano-magnesia, porous nano-titania, porous nano-zinc oxide, and porous nano-calcium oxide; the large-particle-size nano-ceramics are one or more of nano-alumina, nano-boehmite, nano-zirconia, nano-silica, nano-magnesia, nano-titania, nano-zinc oxide, and nano-calcium oxide. The particle size of the small-particle-size porous nano-ceramics is 20 - 80 nm, more preferably 30 - 60 nm, and the particle size of the large-particle-size porous nano-ceramics is 120 - 350 nm, more preferably 150 - 300 nm.

[0018] The dispersants of the first coating and the second coating are both one of sodium citrate, EDTA, HEDTA, sodium stearate, alkyl sulfonate, fatty alcohol polyoxyethylene ether, polyacrylamide or ammonium polymethacrylate; the thickeners of the first coating and the second coating are both one of polyvinyl alcohol, polyacrylate or polyacrylamide; the wetting agents of the first coating and the second coating are both one of branched-chain fatty alcohol polyoxyethylene ether, branched-chain alkylphenol polyoxyethylene ether or branched-chain alcohol polyoxyethylene ether sulfate.

[0019] The binder of the first coating is one of polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC) or polyvinylidene fluoride (PVDF), and the binder of the second coating is one of polyvinyl alcohol, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl acrylate, polyvinyl acetate, polyacrylate, polyurethane or one or more of the copolymer systems derived from the above polymers.

[0020] The present invention also claims to protect the preparation method of the ceramic separator, which includes the following steps:

[0021] (1) Preparation of the first coating slurry: Add ceramic particles to the modified liquid, grind, wash with water and dry to obtain modified ceramics; mix the obtained modified ceramics, dispersant, thickener, binder and wetting agent evenly to obtain the first coating slurry;

[0022] (2) Preparation of the second coating slurry: Add a mixture of small-particle-size porous nano-ceramics and large-particle-size nano-ceramics to the solvent, add a dispersant, a thickener, a binder and a wetting agent, and stir and mix evenly to obtain the second coating slurry;

[0023] (3) Preparation of the ceramic separator: Coat the first coating slurry on one side surface of the base film by microgravure coating, dry to form a functional modified layer, and then coat the second coating slurry on the functional modified layer to obtain the ceramic separator.

[0024] The present invention also claims to protect the application of the ceramic separator in secondary batteries.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) By adding modified ceramics with a polymer coating layer to the first coating, the present invention has excellent electrical conductivity and high thermal stability; and by adding nano-ceramics with different particle sizes to the second coating, the nano-ceramics with larger particle sizes are stacked, and the pores formed are filled with nano-ceramics with smaller particle sizes, increasing the heat resistance of the separator. The nano-ceramics with smaller particle sizes use porous materials to ensure that the overall air permeability of the separator is not affected, and can also provide certain shuttle channels for lithium ions and store a certain amount of electrolyte, enhancing the capacity retention rate and cycle performance of the battery;

[0027] (2) The ceramic separator of the present invention has good high-temperature resistance. In addition, due to the addition of modified ceramics with a polymer coating layer, the puncture resistance of the ceramic separator is improved; at the same time, by adding porous nano-ceramics with different particle sizes, the heat resistance of the separator is increased without affecting the air permeability of the separator, ensuring the stability of battery performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can be obtained based on these drawings.

[0029] Figure 1 It is a schematic diagram of a ceramic separator of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0030] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.

[0031] Example 1

[0032] A method for preparing a ceramic separator includes the following steps:

[0033] (1) Preparation of the first coating slurry: Pyrrole as a modifier and ammonium persulfate as an oxidant were successively added to water in a mass ratio of 1:3:6 and stirred evenly to obtain a modified solution. Alumina, zirconia, and silicon carbide as ceramic particles were mixed in a mass ratio of 6:3:1 and then added to the modified solution. The mass ratio of the ceramic particles to the modified solution was 8:2. Then, it was added to a ball mill for ball milling at a ball milling speed of 300 rpm for 20 h. The ball-milled mixture was washed with deionized water and dried in a vacuum oven to obtain modified ceramic particles. The obtained modified ceramics and water were stirred and mixed, and then a dispersant sodium stearate, a thickener polyvinyl alcohol, a binder polymethyl methacrylate, and a wetting agent branched fatty alcohol polyoxyethylene ether surfactant were successively added and mixed evenly to obtain the first coating slurry. Among them, the mass ratio of the modified ceramic particles, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent was 88:1:3:7:1;

[0034] (2) Preparation of the second coating slurry: Nano-alumina with a particle size of 150 nm and porous nano-alumina with a particle size of 40 nm were mixed and added to water and stirred evenly. Subsequently, a dispersant sodium stearate, a thickener polyvinyl alcohol, a binder polymethyl methacrylate, and a wetting agent branched fatty alcohol polyoxyethylene ether surfactant were successively added and stirred evenly to obtain the second coating slurry. Among them, the mass ratio of the large-particle-size nano-alumina, small-particle-size porous nano-alumina, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent was 70:20:0.5:2:7:0.5;

[0035] (3) Preparation of the ceramic separator: The first coating slurry was coated on one side surface of a 7-μm PP / PE membrane substrate by microgravure coating, dried in an oven with a coating thickness of 1 μm, and then the second coating slurry was coated on the first coating, dried in an oven with a coating thickness of 1 μm, and wound up to obtain the ceramic separator with a thickness of 9 μm.

[0036] Example 2

[0037] A method for preparing a ceramic separator, comprising the following steps:

[0038] (1) Preparation of the first coating slurry: The modifier pyrrole and the oxidant ammonium persulfate were successively added to water at a mass ratio of 1:3:6, and stirred evenly to obtain a modified solution. Alumina, zirconia, and silicon carbide ceramic particles were mixed at a mass ratio of 6:3:1 and then added to the modified solution. The mass ratio of the ceramic particle silicon to the modified solution was 8:2. Then, it was added to a ball mill for ball milling at a ball milling speed of 280 - 320 rpm for 20 h. The ball-milled mixture was washed with deionized water and dried in a vacuum oven to obtain modified ceramic particles. The obtained modified ceramics and water were stirred and mixed, and then a dispersant sodium stearate, a thickener polyvinyl alcohol, a binder polymethyl methacrylate, and a wetting agent branched-chain fatty alcohol polyoxyethylene ether surfactant were successively added and mixed evenly to obtain the first coating slurry. Among them, the mass ratio of the modified ceramic particles, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent was 90:1:2:6:1;

[0039] (2) Preparation of the second coating slurry: Nanometer alumina with a particle size of 150 nm and porous nanometer alumina with a particle size of 40 nm were mixed and added to water, and stirred evenly. Subsequently, a dispersant sodium stearate, a thickener polyvinyl alcohol, a binder polymethyl methacrylate, and a wetting agent branched-chain fatty alcohol polyoxyethylene ether surfactant were successively added and stirred evenly to obtain the second coating slurry. Among them, the mass ratio of the large-particle-size nanometer alumina, the small-particle-size porous nanometer alumina, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent was 70:20:0.5:2:7:0.5;

[0040] (3) Preparation of the ceramic separator: The first coating slurry was coated on one surface of a 7-μm PP / PE membrane substrate by microgravure coating, dried in an oven, and the coating thickness was 1 μm. Then, the second coating slurry was coated on the first coating, dried in an oven, and the coating thickness was 1 μm. The ceramic separator was wound up, and the thickness of the ceramic separator was 9 μm.

[0041] Example 3

[0042] A method for preparing a ceramic separator, comprising the following steps:

[0043] (1) Preparation of the first coating slurry: The modifier pyrrole and the oxidant ammonium persulfate were successively added to water in a mass ratio of 1:3:6, and stirred evenly to obtain a modified solution. The ceramic particles alumina, zirconia and silicon carbide were mixed in a mass ratio of 6:3:1 and then added to the modified solution. The mass ratio of the ceramic particles to the modified solution was 8:2. Then it was added to a ball mill for ball milling. The ball milling speed was 280 - 320 rpm and the ball milling time was 20 h. The ball-milled mixture was washed with deionized water and dried in a vacuum oven to obtain modified ceramic particles. The obtained modified ceramics and water were stirred and mixed, and then the dispersant sodium stearate, the thickener polyvinyl alcohol, the binder polymethyl methacrylate and the wetting agent branched fatty alcohol polyoxyethylene ether surfactant were successively added and mixed evenly to obtain the first coating slurry. Among them, the mass ratio of the modified ceramic particles, sodium stearate, polyvinyl alcohol, polymethyl methacrylate and the wetting agent was 88:1:3:7:1;

[0044] (2) Preparation of the second coating slurry: Nanometer alumina with a particle size of 150 nm and porous nanometer alumina with a particle size of 40 nm were mixed and added to water, and stirred evenly. Subsequently, the dispersant sodium stearate, the thickener polyvinyl alcohol, the binder polymethyl methacrylate and the wetting agent branched fatty alcohol polyoxyethylene ether surfactant were successively added and stirred evenly to obtain the second coating slurry. Among them, the mass ratio of the large-particle-size nanometer alumina, the small-particle-size porous nanometer alumina, sodium stearate, polyvinyl alcohol, polymethyl methacrylate and the wetting agent was 75:15:0.5:2:7:0.5;

[0045] (3) Preparation of the ceramic separator: The first coating slurry was coated on one side surface of a 7-μm PP / PE membrane substrate by microgravure coating, dried in an oven, and the coating thickness was 1 μm. Then the second coating slurry was coated on the first coating, dried in an oven, and the coating thickness was 1 μm. The ceramic separator was wound up, and the thickness of the ceramic separator was 9 μm.

[0046] Example 4

[0047] A preparation method of a ceramic separator, comprising the following steps:

[0048] (1) Preparation of the first coating slurry: The modifier pyrrole and the oxidant ammonium persulfate were successively added to water in a mass ratio of 1:3:6 and stirred evenly to obtain a modified solution. Alumina, zirconia, and silicon carbide ceramic particles were mixed in a mass ratio of 6:3:1 and then added to the modified solution. The mass ratio of the three ceramic particles of alumina, zirconia, and silicon carbide to the modified solution was 8:2. Then, it was added to a ball mill for ball milling at a ball milling speed of 280 - 320 rpm for 20 h. The ball-milled mixture was washed with deionized water and dried in a vacuum oven to obtain modified ceramic particles. The obtained modified ceramics and water were stirred and mixed, and then a dispersant sodium stearate, a thickener polyvinyl alcohol, a binder polymethyl methacrylate, and a wetting agent were successively added and mixed evenly to obtain the first coating slurry. Among them, the mass ratio of the modified ceramic particles, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent branched-chain fatty alcohol polyoxyethylene ether surfactant was 90:1:2:6:1;

[0049] (2) Preparation of the second coating slurry: Nano-alumina with a particle size of 150 nm and porous nano-alumina with a particle size of 40 nm were mixed and added to water and stirred evenly. Subsequently, a dispersant sodium stearate, a thickener polyvinyl alcohol, a binder polymethyl methacrylate, and a wetting agent were successively added and stirred evenly to obtain the second coating slurry. Among them, the mass ratio of the large-particle-size nano-alumina, small-particle-size porous nano-alumina, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent branched-chain fatty alcohol polyoxyethylene ether surfactant was 75:15:0.5:2:7:0.5;

[0050] (3) Preparation of the ceramic separator: The first coating slurry was coated on one side surface of a 7-μm PP / PE membrane substrate by microgravure coating, dried in an oven with a coating thickness of 1 μm. Then, the second coating slurry was coated on the first coating, dried in an oven with a coating thickness of 1 μm, and wound up to obtain the ceramic separator with a thickness of 9 μm.

[0051] Comparative Example 1

[0052] A method for preparing a ceramic separator, comprising the following steps:

[0053] (1) Add the modifier pyrrole and the oxidant ammonium persulfate to water in a mass ratio of 1:3:6, stir evenly to obtain a modification solution. Mix alumina, zirconia, and silicon carbide ceramic particles in a mass ratio of 6:3:1, then add them to the modification solution. The mass ratio of the ceramic particles to the modification solution is 8:2. Then add the mixture to a ball mill and mill at a rotational speed of 280 - 320 rpm for 20 h. Wash the milled mixture with deionized water and dry it in a vacuum oven to obtain modified ceramic particles. Stir and mix the obtained modified ceramics and water, then successively add the dispersant sodium stearate, the thickener polyvinyl alcohol, the binder polymethyl methacrylate, and the wetting agent branched fatty alcohol polyoxyethylene ether surfactant and mix evenly to obtain a coating slurry. Among them, the mass ratio of the modified ceramic particles, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent is 88:1:3:7:1;

[0054] (2) Preparation of the ceramic separator: Coat the coating slurry obtained in step (1) on one side surface of a 7-μm PP / PE membrane substrate by microgravure coating, dry it in an oven, with a coating thickness of 1 μm, and wind it up to obtain a ceramic separator with a thickness of 8 μm.

[0055] Comparative Example 2

[0056] A method for preparing a ceramic separator includes the following steps:

[0057] (1) Preparation of the coating slurry: Take nano-alumina with a particle size of 150 nm and porous nano-alumina with a particle size of 40 nm, mix them and add them to water, stir evenly, then successively add the dispersant sodium stearate, the thickener polyvinyl alcohol, the binder polymethyl methacrylate, and the wetting agent, and stir evenly to obtain a coating slurry. Among them, the mass ratio of the large-particle-size nano-alumina, the small-particle-size porous nano-alumina, sodium stearate, polyvinyl alcohol, polymethyl methacrylate, and the wetting agent branched fatty alcohol polyoxyethylene ether surfactant is 70:20:0.5:2:7:0.5;

[0058] (2) Preparation of the ceramic separator: Coat the coating slurry obtained in step (1) on one side surface of a 7-μm PP / PE membrane substrate by microgravure coating, dry it in an oven, with a coating thickness of 1 μm, and wind it up to obtain a ceramic separator with a thickness of 8 μm.

[0059] Measure the performance of the ceramic separators prepared in Examples 1 - 4 and Comparative Examples 1 - 2:

[0060] For the tests of the puncture strength, air permeability, thermal shrinkage rate, and ionic conductivity of the separator, refer to the national standard GB / T36363 - 2018 "Polyolefin Separators for Lithium-Ion Batteries";

[0061] The following table shows the final test results:

[0062]

[0063] As shown in Table 1, by comparing Examples 1-4 with Comparative Examples 1-2, the ceramic separator prepared by the present invention has excellent puncture strength, ionic conductivity and heat resistance, and its air permeability is still within the range. It can be shown that, while ensuring its air permeability, the ceramic separator prepared by the present application has a relatively high puncture strength and good heat shrinkage performance under an ultra-thin coating, and also has excellent ionic conductivity.

[0064] The above are only the preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A ceramic separator, characterized in that, Comprising: A base film, A first coating disposed on at least one surface of the base film, And a second coating disposed on the surface of the first coating; The first coating comprises a modified ceramic; the second coating comprises a porous nano-ceramic.

2. The ceramic separator according to claim 1, wherein The first coating and the second coating further comprise a dispersant, a thickening agent, a binder and a wetting agent.

3. The ceramic separator according to any one of claims 1-2, characterized in that, The base film is a porous thin film with a thickness of 1μm - 20μm.

4. The ceramic separator according to any one of claims 1-2, characterized in that The modified ceramic is obtained by in-situ polymerization of a polymer coating layer on the surface of ceramic particles with a modifying solution; the material of the ceramic particles is selected from one or more of alumina, boehmite, zirconia, silica, magnesia, titania, zinc oxide and calcium oxide.

5. The ceramic separator according to claim 4, wherein, The modifying solution comprises a modifier pyrrole, an oxidant ammonium persulfate and a solvent.

6. The ceramic separator according to any one of claims 1-2, characterized in that, The porous nano-ceramic comprises small particle size porous nano-ceramics and large particle size nano-ceramics; the small particle size porous nano-ceramics are one or more of porous nano-alumina, porous nano-boehmite, porous nano-zirconia, porous nano-silica, porous nano-magnesia, porous nano-titania, porous nano-zinc oxide and porous nano-calcium oxide with a size of 20 - 80nm; the large particle size nano-ceramics are one or more of nano-alumina, nano-boehmite, nano-zirconia, nano-silica, nano-magnesia, nano-titania, nano-zinc oxide and nano-calcium oxide with a size of 120 - 350nm.

7. The ceramic separator according to claim 2, wherein The dispersant for both the first coating and the second coating is one of sodium citrate, EDTA, HEDTA, sodium stearate, alkyl sulfonate, fatty alcohol polyoxyethylene ether, polyacrylamide or ammonium polymethacrylate; the thickening agent for both the first coating and the second coating is one of polyvinyl alcohol, polyacrylate or polyacrylamide; the wetting agent for both the first coating and the second coating is one of branched-chain fatty alcohol polyoxyethylene ether, branched-chain alkylphenol polyoxyethylene ether or branched-chain alcohol polyoxyethylene ether sulfate.

8. The ceramic separator according to claim 2, characterized in that, The binder for the first coating is one of polyvinyl alcohol (PVA), carboxymethyl cellulose (CMC) or polyvinylidene fluoride (PVDF), and the binder for the second coating is one or more of polyvinyl alcohol, styrene-butadiene rubber, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polymethyl methacrylate, polybutyl methacrylate, styrene-acrylic latex, polyacrylonitrile, ethyl polyacrylate, polyvinyl acetate, polyacrylate, polyurethane or a copolymer system derived from the above polymers.

9. A method for preparing the ceramic separator according to any one of claims 1-8, characterized in that, Including the following steps: (1) Preparation of the first coating slurry: Add ceramic particles to the modifying solution, and obtain modified ceramics through grinding, washing with water and drying; mix the obtained modified ceramics, dispersant, thickening agent, binder and wetting agent evenly to obtain the first coating slurry; (2) Preparation of the second coating slurry: Add a mixture of small particle size porous nano-ceramics and large particle size nano-ceramics to the solvent, add a dispersant, a thickening agent, a binder and a wetting agent, and stir and mix evenly to obtain the second coating slurry; (3) Preparation of the ceramic separator: Coat the first coating slurry on one surface of the base film by microgravure coating, dry it to form a functional modified layer, and then coat the second coating slurry on the functional modified layer to obtain the ceramic separator.

10. Application of the ceramic separator according to any one of claims 1-8 to a secondary battery.

Citation Information

Patent Citations

  • Ceramic diaphragm with high inorganic solid-phase content and application of ceramic diaphragm in lithium ion battery system

    CN104485438A

  • Method for preparing hollow micro-bead ceramic coated diaphragm

    CN108649168A

Cited By

  • Composite coating diaphragm, preparation method thereof and secondary battery

    CN121507324A